Modern concept of autoimmunity in rheumatology - E. L. Nasonov (Научно-практическая ревматология, 2018)
Two fundamental pathologic processes are central to the spectrum of chronic inflammation mechanisms: autoimmunity and autoinflammation.  Autoimmunity and autoinflammation are mutually potent pathologic processes; their development is considered within the framework of the “immunoinflammatory” continuum, reflecting the close relationship between innate and acquired types of immune response. Autoimmunity is the leading mechanism of pathogenesis of a large group of chronic inflammatory human diseases, defined as autoimmune diseases, the frequency of which in the population exceeds 10%. Advances in molecular biology, pharmacogenetics and bioinformatics have created prerequisites for individualization of therapy of autoimmune rheumatic diseases within the concept of personalized medicine.  The study of immunopathogenesis mechanisms, improvement of diagnostics, deciphering the nature of molecular taxonomy, development of approaches to prevention and personalized therapy of human autoimmune diseases is among the priority directions of medicine of the 21st century.